Bank response to higher capital requirements: Evidence from a quasi-natural experiment - Reint E. Gropp; Thomas Mosk; Steven Ongena; Carlo Wix (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
We study the impact of higher capital requirements on banks' balance sheets and its transmission to the real economy. The 2011 EBA capital exercise is an almost ideal quasi-natural experiment to identify this impact with a difference-in-differences matching estimator. We find that treated banks increase their capital ratios by reducing their risk-weighted assets and - consistent with debt overhang - not by raising their levels of equity. Banks reduce lending to corporate and retail customers, resulting in lower asset-, investment- and sales growth for firms obtaining a larger share of their bank credit from the treated banks.
Keywords: 330